Dynamics of Tourists' Experiences Visiting Sustainable Tourism Destinations: Issues and Cases in Sikka Regency, East Nusa Tenggara Province - Paulus Nong Wisang (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Tourist experiences are highly dynamic when visiting sustainable tourism destinations. Their significance is the essence of the tourism product itself. Memorable experiences will make tourists feel happy, subsequently shaping the destination's image and encouraging repeat visits. This research aims to analyse tourist descriptors and typologies, tourist experiences, and formulate directions for the future development of sustainable tourism destination products. This study employs qualitative methods with a multiple case study approach and also hermeneutics in the study of tourism destinations. Findings from this research indicate that tourists visiting consist of various characteristics and are predominantly millennials and zillennials. Their visits are mostly of the allocentric and mid-centric typology, with the latter being very minimal. The experiences gained are very memorable and make tourists feel happy. However, product services need to be improved by managers as tourists still engage in minimal activity attractions. The formulation of supplementary tourism becomes a direction in the future development of spatially-based sustainable tourism destinations. The implications of this research are the development of tourism products that provide memorable experiences and happiness for allocentric tourists to shape the destination's image and also improve the local community's economy.